ANALISIS PENDAPATAN COKELAT BATANGAN RUMAH PRODUKSI EBIER SUTH KABUPATEN MANOKWARI SELATAN - Obadja A. Fenetiruma; Diana N. Irbayanti; Lisma Sadewi (Sosio Agri Papua, 2024)
West Papua Province is one of the cocoa producers which is a superior commodity in the agricultural sector. The area of West Papua Province that has the potential to be a cocoa production center, one of which is southern Manokwari. Areas with potential for cocoa production in the South Manokwari region are spread in Ransiki, Momi waren and Oransbari Districts. Cocoa beans from South Manokwari have various uses, including cocoa beans from the Ebier Suth production house used to produce chocolate bars. Chocolate bars are one of the products derived from cocoa that has great potential to be developed. South Manokwari is known as an area with abundant cocoa production, cocoa beans that are processed into chocolate bar products become commodities that have significant potential and economic value. To ensure the continuity and development of chocolate bars at the Ebier Suth Production House, it is important to analyze the revenue and how the chocolate bar products are sold. Specifically, the purpose of this research is (1) to analyze the income of chocolate bar products from the Ebier Suth Production House, (2) to examine the sales of chocolate bar products at the Ebier Suth Production House. Data was obtained from interviews with respondents based on a list of questions/questionnaires that had been prepared, while secondary data was obtained from related agencies related to this study. Analysis of Chocolate Bar Business at Ebier Suth Production House : 1) The revenue from chocolate bar products at Ebier Suth Production House amounts to IDR 3,920,000 per month. The total sales per month reach 1,320 chocolate bars, equivalent to IDR 22,650,000, with total production costs amounting to IDR 18,730,000. 2) The sales of chocolate bar products at Ebier Suth Production House have equal opportunities and weaknesses, each with a percentage of 40%. Opportunities arise from the sale of chocolate bars through external distributors in the Manokwari and Oransbari regions. Weaknesses stem from fluctuations in product quality, a lack of labor, and the absence of backup machines, which could affect chocolate bar production.